Screwed or cemented dental implant prosthesis? (Research, Society and Development, 2021)
Dental implants became a viable alternative involving the Odontology field developing the aesthetics function and the patient’s comfort. The choice of which type of prosthesis connection is based on their clinical situation of each case and also for own professional preferences. There are two types of prosthetic restorations commonly used in Implantology: the cemented one and the screw retained prosthesis; both have their own advantages and limitations. The decision of which prosthetic method to use starts during the planning stage and can imply the aesthetics, dental occlusion, retention, effect over the peri-implant tissue, among other complications, influencing the implant survival rate. The peri-implant marginal bone loss is one of the problems related to the late failure of the osseointegration of the implants, being a relevant cause of failure, because it may promote the implant removal due to the osseointegration loss. The goal of this study was to analyze and identify the relation of different types of prosthesis (cemented and screw retained) through a literary point, with the peri-implant marginal bone loss, as well as relate the used type of prosthesis with the implant survival rate. Therefore, it is concluded that the marginal peri-implant bone loss owns multifactorial etiology and there are other factors that influence the implant survival, which is not possible to obtain a straight bone loss comparison with the types of prosthesis installed. Nevertheless, the screw-retained prosthesis presented more biomechanical complications such as the screw loosening and the ceramic fracture; and the cemented prosthesis showed more biological complications involving the peri- implant tissues.